Implementation and evaluation of a group peer mentoring and leadership development program for research faculty in academic medicine - Linda H. Pololi; Janet T. Civian; Mark Brimhall-Vargas; Vasilia Vasiliou; Arthur T. Evans; Kacy Ninteau; Lisa A. Cooper; Brian T. Gibbs; Robert T. Brennan (Journal of Clinical and Translational Science)
Abstract